The psychology of chronic post-surgical pain: new frontiers in risk factor identification, prevention and management. Issue 4 (November 2017) - Weinrib, Aliza Z; Azam, Muhammad A; Birnie, Kathryn A; Burns, Lindsay C; Clarke, Hance; Katz, Joel
In an era of considerable advances in anaesthesiology and pain medicine, chronic pain after major surgery continues to be problematic. This article briefly reviews the known psychological risk and protective factors associated with the development of chronic postsurgical pain (CPSP). We begin with a definition of CPSP and then explain what we mean by a risk/protective factor. Next, we summarize known psychological risk and protective factors for CPSP. Psychological interventions that target risk factors and may impact postsurgical pain are reviewed, including the acceptance and commitment therapy (ACT)-based approach to CPSP prevention and management we use in the Transitional Pain Service (TPS) at the Toronto General Hospital. Finally, we conclude with recommendations for research in risk factor identification and psychological interventions to prevent CPSP. Several pre-surgical psychological risk factors for CPSP have been consistently identified in recent years. These include negative affective constructs, such as anxiety symptoms, depressive symptoms, pain catastrophizing and general psychological distress. In contrast, relatively few studies have examined psychological protective factors for CPSP. Psychological interventions that target known psychological risk factors while enhancing protective psychological factors may reduce new incidence of CPSP. The primary goal of our ACT intervention is to teach patients a mindful way of responding to their postsurgical pain that empowers them to interrupt the negative cycle of pain, distress, behavioural avoidance and escalating opioid use that can limit functioning and quality of life while paradoxically amplifying pain over time. Early clinical outcome data suggest that patients who receive care from TPS physicians reduce their pain and opioid use, yet patients who also receive our ACT intervention have a larger decrease in daily opioid dose while reporting less pain interference and lower depression scores.